Erratum: Zahn et al. Manipulation of Medicinal Products for Oral Administration to Paediatric Patients at a German University Hospital: An Observational Study. Pharmaceutics 2020, 12, 583 - Julia Zahn; André Hoerning; Regina Trollmann; Wolfgang Rascher; Antje Neubert (MDPI AG, 2021)
The authors wish to make the following corrections to the affiliation and acknowledgments part [...]